The Origin and Type of Inoculum Determine the Effect of Arbuscular Mycorrhizal Fungi on Tomato under Different Irrigation Regimes - Aracely Mena-Echevarría; Hugo M. Ramírez-Tobias; Heriberto Méndez-Cortés; Ángel Natanael Rojas-Velázquez; Cristian López-Palacios; Reyna P. Hipólito-Piedras (Agronomy, 2024)
Arbuscular mycorrhizal fungi (AMF) play a crucial role in the resilience of plants subjected to water deficit. The objective of this study was to evaluate the impact of AMF from a semi-arid and humid ecosystem, applied as inocula (two monospecific and two consortia), and three irrigation doses (100%, 85%, and 70%) on tomato plant growth. A factorial experiment in a completely randomized design was used. Colonization with monospecific inocula (EH and ES) showed contrasting differences at 85% and 100% irrigation rates. With gradually increasing irrigation rates, colonization decreased with the CH consortium, while the CS consortium showed similar colonization levels at all three irrigation rates. AMF from humid environments (monospecific or in a consortium) did not affect equatorial diameter when the irrigation rate was reduced by 15%, while polar diameter was similar at all three irrigation rates. Inocula from the semi-arid ecosystem promoted the greatest equatorial and polar diameters at the 100% irrigation dose. The monospecific inoculum of C. etunicatum (ES) showed great potential to promote plant growth and development at the 100% irrigation dose and could be a biotechnological tool to improve tomato yield under conditions similar to those of this study.